Lichen: A comprehensive review on Lichens as a natural sources exploring nutritional and biopharmaceutical benefits - Gautam, Ajay Kumar; Yadav, Dhananjay; Singh, Pramod Kumar; Bhagyawant, Sameer S; Jin, Jun-O (Progress in Nutrition, 2021)
Lichens are used as traditional medicines, nutritional value and have been described as a medicine in various pharmacopoeias throughout the world. Lichens are environmental biological indicators for human operations to change the ecosystem and also generate a range of distinctive secondary metabolites with varying biological potential. In addition to their prospective biological role as photoprotection, anticancer, anti-hepatotoxic, antidiabetic, allelopathic, immunomodulatory, etc. Over the past decade, interest in lichens as a source of novel bioactive molecules has been renewed and increasing. The role of secondary metabolites in lichen symbiosis and its medicinal impacts has not been well studied. This review summarizes the present status of characterization, nutritional values, and pharmaceutical properties of lichens and their applications.